2018
DOI: 10.1039/c8ta05735d
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating the nature and behavior of the active center: the key for photocatalytic H2production in Co@NH2-MIL-125(Ti)

Abstract: Insight into the operation at the molecular level of a promising light-driven H2 production system based on Co catalytic sites hosted in a Ti-based MOF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 29 publications
(18 reference statements)
0
36
0
Order By: Relevance
“…Illustratively, Co K-edge XANES spectra were recorded for a freshly suspended cobaloxime@NH2-MIL-125(Ti) composite sample during its in situ incubation in acetonitrile/triethylamine/water (5:1:0.1) mixture and under illumination. 217 The initial spectrum indicated the presence of Co(II) cations and clearly differed from those obtained for the pristine Co(III)-cobaloxime complex. The EXAFS data showed that the Co(II) species exhibited an octahedral first coordination sphere formed by O and/or N atoms at ~2 Å.…”
Section: Xps Xanes Exafs Saxs Spectroscopiesmentioning
confidence: 78%
“…Illustratively, Co K-edge XANES spectra were recorded for a freshly suspended cobaloxime@NH2-MIL-125(Ti) composite sample during its in situ incubation in acetonitrile/triethylamine/water (5:1:0.1) mixture and under illumination. 217 The initial spectrum indicated the presence of Co(II) cations and clearly differed from those obtained for the pristine Co(III)-cobaloxime complex. The EXAFS data showed that the Co(II) species exhibited an octahedral first coordination sphere formed by O and/or N atoms at ~2 Å.…”
Section: Xps Xanes Exafs Saxs Spectroscopiesmentioning
confidence: 78%
“…Under the same conditions, the resulting 2 wt % Pt/CTF‐HC2 shows a rate of 2991 μmol g −1 h −1 for H 2 production (Figure 4b). As displayed in Table S2, 15‐[Ni(pymt) 2 ] n /CTF‐HC2 is slightly higher than that of 2 wt % Pt/CTF‐HC2 photocatalyst and is far superior to Ni(OH) 2 ‐2.5 %/TpPa‐2 (1896 μmol g −1 h −1 ), [32] Co@N 2 ‐COF (782 μmol g −1 h −1 ), [21] Co@COF‐42 (233 μmol g −1 h −1 ), [21] Co@NH 2 ‐MIL‐125 (Ti) (375 μmol g −1 h −1 ), [79] [Co II (TPA)Cl][Cl]@MIL‐125‐NH 2 (553 μmol g −1 h −1 ), [80] and the physical mixing sample of [Ni(pymt) 2 ] n and CTF‐HC2 through grinding at room temperature (1960 μmol g −1 h −1 , Figure S14).…”
Section: Resultsmentioning
confidence: 99%
“…After Nasalevich's work, a few related papers postulated that the Co species in the MOF cages were responsible for accumulating the electrons needed for reducing protons to H 2 . [ 231 ] The Ni NPs have also been incorporated in MOF‐5(Zn) for effective photocatalytic H 2 production. [ 76 ] Before the photocatalytic reaction, a metal complex photosensitizer, Eosin Y (EY), was added on Ni@MOF‐5(Zn) to extend the light absorbance spectrum.…”
Section: Mof Hybrids For Hydrogen Productionmentioning
confidence: 99%